Angiographically defined collateral circulation and risk of stroke in patients with severe carotid artery stenosis. North American Symptomatic Carotid Endarterectomy Trial (NASCET) Group. - Henderson, R; Eliasziw, M; Fox, A; Rothwell, P; Barnett, H (2000)
BACKGROUND AND PURPOSE: Blood supply through collateral pathways improves regional cerebral blood flow and may protect against ischemic events. The effect of collaterals on the risk of stroke and transient ischemic attack (TIA), in the presence of angiographic severe internal carotid artery (ICA) stenosis, was assessed. METHODS: Angiographic collateral filling through anterior communicating and posterior communicating arteries and retrograde filling through ophthalmic arteries were determined in all patients at entry into the North American Symptomatic Carotid Endarterectomy Trial. Kaplan-Meier event-free survival analyses were performed on 339 medically treated and 342 surgically treated patients. RESULTS: The presence of collaterals supplying the symptomatic ICA increased with severity of stenosis. Two-year risk of hemispheric stroke in medically treated patients with severe ICA stenosis was reduced in the presence of collaterals: 27.8% to 11.3% (P=0.005). Similar reductions were observed for hemispheric TIA (36.1% versus 19.1%; P=0.008) and disabling or fatal strokes (13.3% versus 6.3%; P=0.11). For surgically treated patients, the perioperative risk of hemispheric stroke was 1.1% in the presence of collaterals versus 4. 9% when absent. The 2-year stroke risks for surgical patients with and without collaterals were 5.9% versus 8.4%, respectively. Neither comparison in the surgical group was statistically significant. The observed reductions were independent of the degree of ICA stenosis and other vascular risk factors. CONCLUSIONS: Collaterals are associated with a lower risk of hemispheric stroke and TIA, both long term and perioperatively. Angiographic identification of collaterals assists in identifying patients with severe ICA stenosis at lower risk of stroke and TIA.